2016
DOI: 10.2118/179741-pa
|View full text |Cite
|
Sign up to set email alerts
|

Osmosis as Mechanism for Low-Salinity Enhanced Oil Recovery

Abstract: We believe that osmosis has been overlooked as a possible mechanism for observed low-salinity enhanced-oil-recovery (EOR) effects. Osmosis can occur in an oil/water/rock system when injecting low-salinity water, because the system is full of an excellent semipermeable membrane-the oil itself.In the present work, water transport through oil films was visualized both in 2D micromodels and in sandstone cores imaged in a microcomputed tomography (CT). After treating these model systems with hexamethyldisilazane (H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
44
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 93 publications
(51 citation statements)
references
References 20 publications
6
44
1
Order By: Relevance
“…Sandengen and Arntzen (2013) suggested that the increase in the osmotic pressure causes brine expansion and oil displacement. This mechanism was agreed by Sandengen et al (2016), Fredriksen et al (2016), and Fredriksen et al (2017). However, Bartels et al (2017) showed that the osmosis pressure can contribute in the incremental oil recovery, but it is not the primary mechanism of LSWF.…”
Section: Introductionmentioning
confidence: 94%
“…Sandengen and Arntzen (2013) suggested that the increase in the osmotic pressure causes brine expansion and oil displacement. This mechanism was agreed by Sandengen et al (2016), Fredriksen et al (2016), and Fredriksen et al (2017). However, Bartels et al (2017) showed that the osmosis pressure can contribute in the incremental oil recovery, but it is not the primary mechanism of LSWF.…”
Section: Introductionmentioning
confidence: 94%
“…It was observed that brine was effectively trapped by the oil phase in the oil-wet micromodel (see Figure 2.14a) while the water-wet micromodel was unsuccessful in establishing stable pore-sized encapsulations of connate water by oil due to continuous water films on the grain surfaces (see Figure 2.14b). [34] After stable encapsulations of connate water had been verified, low-salinity waterflooding was initiated in the oil-wet micromodel. Deionized water was used as the low-salinity water.…”
Section: Visualization Experiments Using 2d Micromodelsmentioning
confidence: 99%
“…Stable encapsulations of connate water were observed in the oil-wet micromodel, but not the water-wet micromodel. [34] shows the complete waterflooding sequence initiated after the visual verification of the stable connate water encapsulations. Connate water contraction was observed in a similar experiment performed when using deionized water as connate water and high-salinity brine as injection fluid.…”
Section: Visualization Experiments Using 2d Micromodelsmentioning
confidence: 99%
See 2 more Smart Citations